Pelatihan Penerapan Streamlining Production Flow dalam Upaya Continuous Improvement di Pabrik Mie Ho Kie San, Patikraja - Florence Leony; Vivi Arisandhy; David Try Liputra; Kartika Suhada; Victor Suhandi; Rainisa Maini Heryanto; Rudy Wawolumaja; Chandra Wiranata; Cindy Felicia Wisanta; Kharens Emerentia; Lea Mashari; Mellisa Pricilia Hambali (Universitas Muhammadiyah Semarang, 2024)
Ho Kie San Noodle Factory is one of the MSMEs in Patikraja District, Central Java that produces traditional noodles. Previously, the community service team had assisted this partner in increasing its production potential. However, there are still many improvements that can be made. The management conveyed the need for Kaizen (continuous improvement) material. Therefore, community service activities were carried out again in this factory. The method used is training. There were 9 participants who attended, representing the human resource department, finance department, general department, administration department, technical department, production department, inventory department and marketing department. The stages of the activities carried out were factory surveys and interviews with management, training implementation preparation, compiling training materials, filling preliminary questionnaires, training to representatives of each department within the company regarding the concept of continuous improvement and streamlined, and filling evaluation questionnaires. Based on the results of the questionnaire, it was found that the level of understanding of the participants increased after the training. Providing materials of Kaizen (continuous improvement) as well as production flow streamlining can help participants in streamlining the flow in each department and can also give motivation to continue making improvements in each department.